Бинаризация и идентификация объектов 2D-отображений параметрических полей электроэнергетических объектов - Мазманян, P.O. (Електротехніка і електромеханіка, 2011)
This article describes parametric fields images binarization and a record coordinate format for storage elements and identifiers of binary images in power equipment condition monitoring systems.. A deterministic method of topologic coupling detection between elements of binary images is given, samples of image binarization and results of test images objects identification presented.